Adat, Islam, and the Idea of Religion in Colonial Indonesia - Mufdil Tuhri; Samsul Maarif; Rikardo Simarmata (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
Based on some early anthropological accounts, people understand adat as any traditional practice: including visiting graves and forest, belief in supernatural powers, and other rituals and ceremonies. Practically speaking, people have not differentiated between the term adat and the encompassing traditions, customs, laws, and others. However, the discourse of religion has influenced the comprehensiveness of the idea of adat. This paper describes the construction of adat through the colonial period, a time dominantly influenced by the discourse of religion. I argue that the colonial construction of adat has strongly impacted religion in Indonesia. Adat which became a contested term and used by the rulers has declined the religious dimension of adat. The construction of adat and the disposition of adat from religion was influenced by various factors including colonial policies. This paper identified three dominant discourse of adat as political construction in colonial Indonesia: firstly, adat as animism was considered as the practices which are not religious, uncivilized and primitive; secondly, the mainstream of adat law has concerned on the secular aspect of adat while neglected the religious dimension of adat; thirdly, the construction of adat as not religion subsequently strengthened the Islamic identity and stressed the adat as opposed to Islam.